Factors influencing access to early childhood services in occupational therapy - Khan, Humaira (My University, 2019)
South Africa is a developing country which is facing numerous challenges. Among these is the issue of caregivers of children with developmental problems accessing early childhood intervention (ECI) services. Bertha Gxowa hospital is a district hospital situated in Germiston, running a multidisciplinary ECI service that includes occupational therapy. The service was underutilised, with poor or late access by caregivers, thereby decreasing the effectiveness of ECI. It was unclear who was accessing these services or whether these services were being accessed timeously and appropriately. The purpose of this study was to describe the characteristics of the population of caregivers and their children who accessed Occupational Therapy services for the first time and to investigate the factors (both barriers and facilitators) that influenced why caregivers accessed Occupational Therapy services for their children. Using a non-standardised, interview-based questionnaire developed by the researcher, the study collected data from 16 participants to determine who was accessing ECI services and what were the factors influencing access. It was noted that mostly mothers were the primary caregivers of children accessing services and children accessing services were over the age of two years. It was found that there were both barriers and facilitators influencing access to the services. Although there were some facilitators, mostly barriers were identified. These were related to cost of transport, caregiver knowledge of developmental norms in children as well as awareness of the existence of the services. Limited information was available from caregivers who did not arrive for their appointments to determine influencing factors for not accessing ECI services. This study has highlighted the need for more research to be conducted on children accessing early childhood services and the factors influencing their access to such services. This would prove beneficial and eliminate some of the barriers hindering access to early childhood services.
A Research Report submitted to the Faculty of Health Science, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy August 2019
Keywords: Occupational Theraphy; Developmental disabilities; Community Health Services